Reconstruction of interactions in the ProtoDUNE-SP detector with Pandora - Abud,AA; Abi,B; Acciarri,R; Acero,MA; Adames,MR; Adamov,G; Adamowski,M; Adams,D; Adinolfi,M; Adriano,C; Aduszkiewicz,A; Aguilar,J; et al. (European Physical Journal C: Particles and Fields, 2023)
The Pandora Software Development Kit and algorithm libraries provide pattern-recognition logic essential to the reconstruction of particle interactions in liquid argon time projection chamber detectors. Pandora is the primary event reconstruction software used at ProtoDUNE-SP, a prototype for the Deep Underground Neutrino Experiment far detector. ProtoDUNE-SP, located at CERN, is exposed to a charged-particle test beam. This paper gives an overviewof the Pandora reconstruction algorithms and how they havebeen tailored for use at ProtoDUNE-SP. In complex eventswith numerous cosmic-ray and beam background particles,the simulated reconstruction and identification efficiency fortriggered test-beam particles is above 80% for the majorityof particle type and beam momentum combinations. Specif-ically, simulated 1 GeV/c charged pions and protons arecorrectly reconstructed and identified with efficiencies of86.1±0.6% and 84.1±0.6%, respectively. The efficiencies measured for test-beam data are shown to be within 5% ofthose predicted by the simulation.